274 Chemical intolerance is not a good predictor of work related symptoms among finnish office workers. (24th April 2018) - Stengård, Jari H; Lappalainen, Sanna; Remes, Jouko; Sainio, Markku
Abstract : Introduction: Chemical intolerance (CI) is a condition characterised by series of symptoms that affected persons attribute to exposure to low levels of several identifiable or unidentifiable substances commonly present in environment. Many of the symptoms are general symptoms, such as dizziness, fatigue, headache and difficulties to concentrate that are present in many medical conditions and illnesses. Similar symptoms are attributed to poor indoor air quality, for instance. In this study we evaluate: occurrence of CI among Finnish office workers and whether identified CI individuals have work related symptoms. Methods: The study population comprises 174 office workers recruited in connexion with our Multispace Office (MOSI) project. The participants work in six different workplaces, of which none had known abnormal sources of indoor air impurities. The Chemical exposure-section of Quick Environment Exposure Sensitivity Inventory (QEESI) questionnaire was employed to identify CI individuals and modified MM-40 (Örebro) questionnaire to evaluate their work related symptoms. Results: We identified altogether 52 (30%) CI individuals as indicated by their QEESI questionnaire score (score ≥40). Of them 21 (40% versus 18% in individuals with QEESI score <40, p<0.002) reported that they have had irritation symptoms in throat, nose or eyes at work and 29 (56% vs 39%, p=0.511) had general symptoms, such as fatigue, headache, feeling heavy head or difficulties in concentrating. Probability of irritation symptoms among CI individuals is 40%. Discussion: Our findings are in line with earlier observations that prevalence of chemical intolerance may be up to 33%. Occurrence of IC was associated with irritation symptoms but not general symptoms. However, its positive predictive value (i.e. proportion of irritation symptoms among CI individuals, 40%) was not much better than prevalence of irritation symptoms among office workers (25%) suggesting that CI is not very good predictor of work related symptoms among Finnish office workers.